Performance of four newly released cassava varieties in a fallowed land over two cropping seasons - Ossai, C.O.; Ojobor, S.A.; Ogwuche, T.O.; Akpeji, S.C.; Sunday, A.I.; Diebiru-Ojo, E.M. (2025)
Cassava (Manihot esculenta Crantz) is an important crop for humans due to its staple and industrial values. Currently the demand is more than the supply as the current output falls below the expected. This necessitated the breeding of superior genotypes that are high yielding. These superior genotypes also requires a fertile soil for optimum production. However, this has been primarily achieved through the application of organic manures and inorganic fertilizers. It is then important to evaluate four newly released cassava varieties in an organically enriched soil relative to the local best variety. Four newly released cassava varieties, Hope, Obasanjo2, Baba 70, and Game changer, and one Local Best (LB) was planted in 5-years fallowed farm lands at three plots (A, B and C) for 2 seasons. It was a three-way factorial (5-varieties*3-farms*2-seasons) arranged in a randomized complete block design and replicated three times. Data were taken on the Fresh Tuber Weight (FTW) and Stem Height (SH) per variety, and pre and post soil status. Data were analyzed using analysis of variance, while differences in varietal means were separated using least significant differences at 5% level of significance. The FTW and SH differed significantly across varieties, years and interaction between variety, farms and year, and ranged from 19.2 ± 0.5 (LB) to 41.0 ± 0.5 (Obasanjo2), 32.1 ± 0.4 (farm C) to 34.1 ± 0.4 (farm A), 30.4 ± 0.3 (year two) to 35.0 ± 0.3 (year one), and the interactions between variety and year, farms and year, and variety, year and farms were significant. The soil macro and micro elements declined in the post relative to the pre status. The fresh yield of the improved varieties Baba70, Game change, Hope and Obasanjo2 was 74%, 80.8%, 81%, and 113% higher than the local best, respectively. Yield declined in the second season due to decline inherent soil nutrient hitherto compensated by shifting cultivation in the farming community.